Optimalisasi Pelaksanaan Pembinaan Residivis Narapidana Narkotika pada Lembaga Pemasyarakatan - Samsu, S.; Yasin, H. M. (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
This study uses primary data through research surveys obtained directly from the research site, in this case, the Class II-A Watampone Prison, to produce secondary materials in the form of interviews and observations. Secondary data through a research survey obtained from data provided by the staff of Class II-A Watampone Prison regarding the development of narcotics convicts recidivists. The data were obtained using the library method or known as document study. The results of this study indicate that the implementation of the Narcotics Prisoner Recidivist training carried out by the Class II-A Watampone Prison has been running according to the provisions of Law no. 12 of 1995, where the coaching and guidance of the Correctional Assistance Citizens consist of two patterns, namely the Personality Development Pattern and the Independence Development Pattern. The implementation of the Narcotics Prison Recidivist Development at the Watampone Class II Penitentiary is considered not optimal because it is influenced by two factors: internal factors consisting of the quality of human resources, facilities and infrastructure, and budget constraints. Meanwhile, external aspects of related institutions have not been optimal in carrying out coaching due to public acceptance.